Spontaneous extinguishing of a vacuum arc in terms of the ecton model; Proceedings of the 18th International Symposium on Discharges and Electrical Insulation in Vacuum, ISDEIV, Eindhoven, august 17-21, 1998; Vol. 1 - Barengolts S. A. (1998, 1998)
В фонде НТБ ТПУ отсутствует